Effects of testosterone hormone and ages on carcass characteristics of Kacang doe - Didik Rudiono (Indonesian Center for Animal Research and Development (ICARD), 2007)
Forty Kacang doe (average initial BW, 10.2 kg) were used in 4x2 factorial arrangement to determine carcass characteristics. Dose of the testosterone as first factor were assigned to four levels, i.e.: control (T0), 1 dose of testosterone propionate (T1), 2 doses of TP (T2), and 3 doses of TP (T3). The age of animals as the second factor, i.e.: 7-8 months of age (U1) and 9-12 months of age (U2), referred to chevon method. The treatment combinations were replicated 5 times, respectively, so that there were 40 heads of doe. Animals were injected with 0.77 mg of TP/kg BW/d weekly for first dose and the goats were fed for 90 days. The diet were assigned to met or exceed 50 g ADG. The variables included slaughter weight, carcass weight, pelt weight, and Kidney Pelvic Heart (KPH) fat weight. There were significant interaction (P<0.01), except on KPH weight. The best carcass characteristics were significantly resulted from injection of 49 mg TP head-1 week-1 treated on 9 kg of Kacang doe. Key Words: Testosterone, Age, Carcass Characteristic, Kacang Doe